Rules for the summer - Quinn, Meghan (Bloom Books, an imprint of Sourcebooks, 2026)
"He clicked "yes" on a dare. She bought a failing candy shop. Now they're neighbors for the summer--and neither is ready for what comes next. Renley Gossage has one shot to prove she's more than Cape Meril's favorite cautionary tale: restore her favorite candy shop before the town writes her off like they did her father. No help, no shortcuts, and definitely no rich men wielding engagement rings and making things messy. Theo Williams never planned on ending up in Cape Meril. A drunken game of truth or dare turned into a botched online engagement, and now he's across the ocean, escaping his father's control with nothing but designer shoes, misplaced confidence, and a rental next door to Renley. She's practical, stubborn, and covered in paint. He's posh, persistent, and willing to use a sander if it means earning her trust. Between collapsing drywall, gossiping neighbors, and the chaotic schemes of Renley's aunt, their forced proximity turns into something dangerously close to real. But Renley's future depends on standing on her own two feet, and Theo's past isn't done with him yet. By the time the candy shop doors open, they'll have to decide if this is just a summer fling--or the happily ever after neither of them saw coming."--Amazon.